Annual reviews of computational physics IX - Stauffer, Dietrich (World Scientific, 2001)
Computational Physics has as a special feature a comprehensive compendium of interatomic potentials as used for materials properties. Other articles deal with simulations of magnetic nanostructures, improved Monte Carlo methods